On-line Partial Discharge Detection for High Voltage Rotating Machines Using Inductive Method - Daukšys, G.; Jonaitis, A. (Elektronika ir Elektrotechnika, 2013)
The solid insulations of electrical equipment are perpetually affected by various duration overvoltages. Electric stress of insulation depends on its thickness and amplitude of applied voltage. The damaged solid insulation may also influence characteristic parameters of partial discharges. The characteristic parameters of solid insulation quality should be permanently evaluated. Partial discharge monitoring provides reliable information necessary for basic maintenance of stator windings of motors and generators. Submitted paper deals with partial discharge measurements in stator windings during the increasing of applied voltage. DOI: http://dx.doi.org/10.5755/j01.eee.19.6.1902